Mesin Unrelated Parallel dengan Mempertimbangkan Multi-task Simultaneous Supervision Dual Resources Constraints (MTSSDRC) untuk Meminimasi Makespan: Model Penjadwalan untuk Mesin Unrelated Parallel dengan Mempertimbangkan Multi-task Simultaneous Supervision Dual Resources Constraints (MTSSDRC) untuk Meminimasi Makespan - Rugova, Akbar; Sukoyo; Akbar, Muhammad (Journal of Research in Industrial Engineering and Management, 2024)
To maximize their production, many companies invest their funds into a semi-automatic machine to help them reach their fullest potential. However, many forgot to also take into account the adjustments that have to be done to the preexisting schedule because of the idle time that operators have now that the new machine has arrived. Multi-task simultaneous supervision dual resource constraints (MTSSDRC) have been the go-to method to solve that problem. Nonetheless, there is still an absence in an MTSSDRC field that involves an Unrelated Parallel Machine Scheduling Problem (UPMSP). This research proposed a model of MTSSDRC that is in line with UPMSP where the machine is a complex system and variations of machining speed can happen from a certain machine to certain jobs. This research also brought MTSSDRC closer to its real-life counterpart as a shop floor that exists in many manufacturing industries.